PERKEMBANGAN ANALISA GULA SECARA KLT DAN KCKT*) - Julia Kantasubrata; Sri Sumartini (Jurnal Kimia Terapan Indonesia, 1992)
Analysis of sugars plays an important role, mainly in foods. Up to now, the search of spesific, selective, reproducible and accurate methods for sugar analysis is still being made. Sugars in foods consist of monosacharides, disacharides and trisacharides. Using conventional and spectrophotometric methods, which are based on measuremen of physical properties or chemical reactions, such individual amount of sugars can not be determined. The emergence of chromatographic techniques has initiated the development of individual sugar analysis. Thin layer chromatography (TLC) is widely used in sugar analysis, since is is simple, cheap, fast and ir has a capability to analyse several samples sinwltaneously. Commonly, lie analysis of sugars is conducted using silica gel as stationary phase. Satisfactory separation could only be produced with impregnated silica plates and multiple TLC runs. In order to reduce the separation time, new stationary phase was developed. The rapid separation of sugars has been achieved by using HPTLC plates Si 50000. In line with the development of bonded phase column, analysis of sugar using HPLC method has received considerable attention, using among others ion exchange columns, amino bonded silica phase, diol and C-18 columns. A relatively new type of sugar separation with a silica based column and eluen containing polyamine reagent has been developed by WATERS. This technique is called a SilicaAmine Modifier (SAM), in which the formation of Schiff base can be eliminated, the life time of the column becomes longer and better monosacharide separation can beproduced compared to other HPLC techniques.